Generation Scotland - Using Electronic Health Records for Research - Archie Campbell; David Porteous (International Journal of Population Data Science, 2018)
Generation Scotland: Scottish Family Health Study (GS:SFHS) is a family-based genetic epidemiology study of ~24,000 volunteers from ~7000 families recruited across Scotland between 2006 and 2011 with the capacity for follow-up through record linkage and re-contact. Broad consent was obtained for linkage to “medical records” for 98% of the cohort.